Editorial - Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
Editorial Sirichai Preudhikulpradab, Ph.D. Program Director, Master of Management (Organization Development and Management) Assumption University, Bangkok, Thailand This issue of the ABAC ODI Journal, Volume 6 comprises of 10 articles, contributed by 15 authors. Each author represents different professions (e.g., graduate students, university professors, researchers and organization development practitioners) and various nationalities (e.g., Thailand, United Kingdom, China, Philippines and Vietnam).